2002
DOI: 10.1248/cpb.50.703
|View full text |Cite
|
Sign up to set email alerts
|

Improved Synthesis and Molecular Modeling of 4.BETA.,19-Dihydroxyandrost-5-en-17-one, an Excellent Inhibitor of Aromatase.

Abstract: Aromatase is a cytochrome P-450 enzyme complex responsible for the conversion of the 4-en-3-one androgens, androst-4-ene-3,17-dione (AD) and testosterone, into estrogens, estrone and estradiol. [1][2][3] Aromatization of the androgens is thought to proceed through three sequential oxygenations at the C-19 position, respectively. [4][5][6] In the third step, the angular methyl group at C-19 and 1b,2b-hydrogens are eliminated to result in the aromatization of the A-ring of the androgen molecule to form estrogen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…They are essential in the synthesis of important drugs such as (S)-timolol, a -adrenergic blocking agent, indinavir, a HIV protease inhibitor, and diltiazem, a calcium channel blocker. In the steroid field, several 4,5-epoxysteroids are intermediates in the synthesis of biologically active compounds like aromatase inhibitors 18,19 and anti-HIV agents 20,21 among others. 22 Furthermore, ringopening of 5R,6R-epoxysteroids gives access to contraceptives, anti-inflammatory agents, and enzymatic inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…They are essential in the synthesis of important drugs such as (S)-timolol, a -adrenergic blocking agent, indinavir, a HIV protease inhibitor, and diltiazem, a calcium channel blocker. In the steroid field, several 4,5-epoxysteroids are intermediates in the synthesis of biologically active compounds like aromatase inhibitors 18,19 and anti-HIV agents 20,21 among others. 22 Furthermore, ringopening of 5R,6R-epoxysteroids gives access to contraceptives, anti-inflammatory agents, and enzymatic inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the steroids which have been studied as aromatase inhibitors are analogues of androstenedione, with substituents at C4, C6, C7 and C19 (Numazawa et al, 2002). Several 6-and 7-substituted analogues of androstenedione are powerful inhibitors of human placental aromatase (Njar et al, 1995).…”
Section: Commentmentioning
confidence: 99%
“…The 5 steroids are¯at, whereas the 5 epimers are bent at the A/B ring junctions. Structure±activity relationships and recent aromatase modelling studies have revealed the existence of a hydrophobic binding pocket with a limited accessible volume in the region corresponding to the side, rather than the side, of the C4, C6 and C7 positions of the androstenedione substrate (Numazawa et al, 2002).…”
Section: Commentmentioning
confidence: 99%